Avoidance of Profound Hypothermia During Initial Reperfusion Improves the Functional Recovery of Hearts Donated After Circulatory Death. Issue 3 (18th January 2016) - White, C. W.; Ambrose, E.; Müller, A.; Li, Y.; Le, H.; Thliveris, J.; Arora, R. C.; Lee, T. W.; Dixon, I. M. C.; Tian, G.; Nagendran, J.; Hryshko, L. V.; et al.
Abstract : The resuscitation of hearts donated after circulatory death (DCD) is gaining widespread interest; however, the method of initial reperfusion (IR) that optimizes functional recovery has not been elucidated. We sought to determine the impact of IR temperature on the recovery of myocardial function during ex vivo heart perfusion (EVHP). Eighteen pigs were anesthetized, mechanical ventilation was discontinued, and cardiac arrest ensued. A 15‐min standoff period was observed and then hearts were reperfused for 3 min at three different temperatures (5°C; N = 6, 25°C; N = 5, and 35°C; N = 7) with a normokalemic adenosine–lidocaine crystalloid cardioplegia. Hearts then underwent normothermic EVHP for 6 h during which time myocardial function was assessed in a working mode. We found that IR coronary blood flow differed among treatment groups (5°C = 483 ± 53, 25°C = 722 ± 60, 35°C = 906 ± 36 mL/min, p < 0.01). During subsequent EVHP, less myocardial injury (troponin I: 5°C = 91 ± 6, 25°C = 64 ± 16, 35°C = 57 ± 7 pg/mL/g, p = 0.04) and greater preservation of endothelial cell integrity (electron microscopy injury score: 5°C = 3.2 ± 0.5, 25°C = 1.8 ± 0.2, 35°C = 1.7 ± 0.3, p = 0.01) were evident in hearts initially reperfused at warmer temperatures. IR under profoundly hypothermic conditions impaired the recovery of myocardial function (cardiac index: 5°C = 3.9 ± 0.8, 25°C = 6.2 ± 0.4, 35°C = 6.5 ± 0.6 mL/minute/g, p = 0.03) during EVHP. We conclude that the avoidance of profound hypothermia during IR minimizes injury and improves the functional recovery of DCD hearts. Abstract : The authors investigate how cardioplegia temperature delivered during the initial reperfusion of hearts donated after circulatory arrest impacts donor organ resuscitation, and demonstrate that the avoidance of profound hypothermia minimizes injury and optimizes functional recovery. See the editorial from Peter MacDonald onpage 737 .